Role of chloroform and dichloromethane solvent molecules in crystal packing: an interaction propensity study. Issue 4 (26th February 2016) - Allen, Frank H.; Wood, Peter A.; Galek, Peter T. A.
Abstract : Using the Cambridge Structural Database (CSD), it is shown that the acidic C—H donors of chloroform and dichloromethane, respectively, form hydrogen bonds with N, O, S, halides or carbon‐bound halogens in 82% and 77% of structures in which such interactions can occur. This hydrogen‐bond potency is retained to a significant degree even in the presence of the more conventional O—H and N—H donors. The hydrogen‐bond propensities exhibited by the C—H protons in CHCl3 and CH2 Cl2 are similar to those of the acetylenic C—C[triple‐bond]C—H proton. However, involvement of the Cl atoms of CHCl3 and CH2 Cl2 in non‐bonded interactions is rather limited: the propensities for formation of (O or N)—H...Cl bonds are only 6% in both cases, while the propensities for the formation of halogen–halogen bonds is generally < 15%, with only Cl...Br interactions having slightly higher values. While C(phenyl)—H...Cl interactions are commonly observed, they are of low propensity and have distances at the upper end of the van der Waals limit. We conclude that the acidic C—H protons in chloroform and dichloromethane solvent molecules play a clear role in the involvement of these molecules in molecular aggregation in crystal structures, and this is exemplified by hydrogen‐bond predictions made using the statistical propensity tool which is now part of the CSD system.